Bilateral Vocal Nodules Multidimensional Assessment: Pre- and Post- Speech Language Pathology Intervention - Rita Alegria; Susana Vaz-Freitas; Fátima Maia; Maria Conceição Manso (MDPI AG, 2023)
(1) Background: Vocal fold nodules are bilateral lesions that can have an important negative impact on a person's job performance, social interaction, and quality of life. This study aims to analyze multidimensional voice evaluation outcomes in a group of patients with bilateral vocal fold nodules who underwent voice therapy. (2) Methods: A retrospective analysis was performed in 42 patients on the following voice evaluations, before and after voice therapy: visual-perceptual (video-laryngostroboscopic evaluation), auditory-perceptual voice analysis based on the GRBAS scale, and aerodynamic voice analysis. Data were collected from January 2001 to December 2019. Data analyses were performed with non-parametric tests (Wilcoxon test) using α = 0.05. (3) Results: The patient average age was 33.6.1 ± 10 years (range 19-60), and 95.2% were female. Voice therapy was delivered by an experienced speech-language pathologist once a week, with an average of 9.8 ± 3 appointments (range 8-17). Vocal fold lesions disappeared in 40.4% of the patients after voice therapy, especially in participants receiving early voice therapy (p = 0.035). When comparing pre- and post-therapy audio-perceptual results, all parameters were improved with statistical significance (p < 0.05) except for the asthenic voice scale. Aerodynamic parameters were all improved but without statistical significance (p > 0.05); (4) Conclusions: Early timing to initiate voice therapy after the onset of symptoms or diagnosis seems to be an important factor for the success of voice therapy (absence of vocal fold nodules).